Exploring the Intersection of Technology and Change Management: Insights from IT Professionals - Eri Kusnanto; Yessica Amelia; Ruslaini Ruslaini (Journal of Economic and Leadership, 2024)
This qualitative research aims to investigate the nexus between technology adoption and change management practices as perceived by IT professionals. Grounded in a constructivist paradigm, the study employs semi-structured interviews to gather rich insights from a purposive sample of IT professionals. Thematic analysis is utilized to identify patterns, themes, and underlying meanings in the data. Results reveal nuanced perspectives on how technology influences organizational change initiatives and the strategies employed by IT professionals to navigate such transformations. The findings contribute to a deeper understanding of the complexities inherent in integrating technology with change management, providing valuable insights for both academia and practitioners in optimizing organizational change processes.